The Effect of Weights and Measurements Usage in Business among the Urban based Fruits and Vegetables Market Sellers in Dar es salaam - Kirumirah, Mubarack Hamidu; Munishi, Emmanuel (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Despite the critical role played by weights and measurements in business and more specifically in the area of fresh fruits and vegetables trade, still little is known about the utilisation of weights and measures among fresh fruits and vegetable traders in big markets in Dar es salaam. In this study, we specifically assessed the usage of weights and measurements among fresh fruits and vegetables in markets. What causes low usage of weights and measures instruments among informal traders and what impact does the use of weights and measures has on traders’ businesses. The study was conducted in Dar es Salaam City at ilala and Stereo markets and used mixed methods approach with a sample of 200 respondents. Data were collected through questionnaire and in-depth interviews. Data were analysed descriptively by SPSS and content analysis manually. Findings provide that there is low usage of standard weighing and measuring instruments among fruits and vegetable traders in the markets and this was majorly caused by low awareness, traders perception and inadequate inspections. The study recommends periodic training to traders on the importance of using standard weights and measures in the businesses.